2021
DOI: 10.1371/journal.pone.0242978
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood metabolome differs in relation to delivery mode, birth order and sex, maternal diet and possibly future allergy development in rural children

Abstract: Allergy is one of the most common diseases among young children yet all factors that affect development of allergy remain unclear. In a small cohort of 65 children living in the same rural area of south-west Sweden, we have previously found that maternal factors, including prenatal diet, affect childhood allergy risk, suggesting that in utero conditions may be important for allergy development. Here, we studied if metabolites in the umbilical cord blood of newborns may be related to development of childhood al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
2
15
1
Order By: Relevance
“…[42] As such, increased cellular energy requirement and a disrupted TCA cycle might be hypothesized, especially since mitochondrial function and elevated serum IgE levels are known to be correlated. [53][54][55] Moreover, a disrupted TCA cycle early in life could be hypothesized due to decreased levels of the TCA intermediates isocitrate and 𝛼-ketoglutarate in cord blood, [56] with the latter being a key molecule in the determination of the overall rate of the TCA cycle. [43]…”
Section: Biomarkers Related To Carbohydrate and Energy Metabolismmentioning
confidence: 99%
“…[42] As such, increased cellular energy requirement and a disrupted TCA cycle might be hypothesized, especially since mitochondrial function and elevated serum IgE levels are known to be correlated. [53][54][55] Moreover, a disrupted TCA cycle early in life could be hypothesized due to decreased levels of the TCA intermediates isocitrate and 𝛼-ketoglutarate in cord blood, [56] with the latter being a key molecule in the determination of the overall rate of the TCA cycle. [43]…”
Section: Biomarkers Related To Carbohydrate and Energy Metabolismmentioning
confidence: 99%
“…Metabolites previously associated with manifest allergy. We selected metabolites for targeted analyses from 13 previously published studies [34][35][36][37][39][40][41][42][43][45][46][47][48] where associations between metabolites and allergic outcomes were found, 151 metabolites based on analysis of plasma, 20 on urine and 11 on exhaled breath. Of all the 182 metabolites that were associated with manifest allergy in these studies, we found five of them in cord plasma to be associated with future allergy in our study.…”
Section: Metabolites Associated With Immune Cell Maturationmentioning
confidence: 99%
“…Focusing on predictive biomarkers could help to identify individuals at risk before the onset of symptoms as well as to help identify targets for preventive strategies. In a previous pilot study in a smaller cohort, we have prospectively predicted allergy development from the umbilical cord plasma GC–MS/MS metabolome 45 . To extend this, we here investigate the cord blood metabolome as well as the maternal metabolome in a larger cohort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that used GC–MS to retrospectively analyse the metabolome in preserved umbilical cord blood from 44 children (who were 8 years old at the time of the study) showed that, among several modulatory factors, sex also had a significant influence on observed differences in metabolic pathways and their possible impact on the subsequent development of allergy [ 131 ]. This study showed that sex significantly influenced branched amino acid metabolism and vitamin B6 metabolism.…”
Section: Reproducibility and Stability Of Asthma-related Metabolic Signatures: Of Validation Cohorts Time Stability Age Sex And Other Facmentioning
confidence: 99%